Food policy volatility and EU policies - Johan Swinnen; Louise Knops; Kristine Van Herck (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Changes in global food prices have affected EU producers and consumers and have triggered policy reactions through the EU's political process. In particular, the EU and member states responded by social policies to protect their consumers, attempts to regulate 'speculation' on agricultural commodities, revisions of sustainability requirements for biofuels, international development and food aid, and changes in the EU's Common Agricultural Policy (CAP). With the exception of biofuel regulations, policy changes have been relatively limited and the effects on global food markets minor. The reasons are that the impact of global price volatility on EU consumers has been limited and the link between the CAP and the world market is much smaller than it was twenty years ago.
Keywords: H2; Q1; 330; food prices; EU policies; biofuels; Common Agricultural Policy; political economy; Lebensmittelpreis; EU-Agrarpolitik; EU-Staaten